Influence of Phosphate Powder Application on The Biology and Demographic Statistics of Green Ladybug (Nezara viridula L.) (Hemiptera: Pentatomidae) on Soybean Pods - Septiani, Rohma Wulan; Rahardjo, Bambang Tri; Widjayanti, Tita (Journal of Tropical Plant Protection, 2023)
Green ladybug Nezara viridula (Hemiptera: Pentatomidae) is one of the harmful pests on soybeans. One of the ways to suppress attacks is by using phosphate fertilizers. The effect of applying phosphate fertilizer could be seen using biological parameters and demographic statistics. The research was conducted at the Pest and Wirehouse Laboratory, Department of Plant Pests and Diseases, Faculty of Agriculture, Brawijaya University, from January to June 2022. The experimental design in this study used Completely Randomized Design (CRD) in the laboratory and wired house. There were four treatment doses of phosphate fertilizer consisting of 0 kg/ha (control), 25  kg/ha (low), 50 kg/ha (recommendation), and 75 kg/ha (high). Observations were made on 90 individuals of N. viridula in each treatment divided into three replications. The type of phosphate fertilizer used in this study was SP36 fertilizer. The observational variables of this study were the biology and demographic statistics of N. viridula. Observations were made daily, and the data were compiled in a live table. Calculations were carried out using demographic statistics and analysis of variance to determine differences between treatments using HSD 5%. The results showed biological and demographic statistical differences in N. viridula: personality, life cycle, and gross growth rate (GRR). These findings have significant implications for pest management in soybean cultivation, suggesting that applying phosphate fertilizers can effectively suppress the attacks of N. viridula, particularly at the recommended dose.